Change in quality of life for patients with irritable bowel syndrome following referral to a gastroenterologist: a cohort study - Canavan, Caroline; West, Joe; Card, Timothy R. (Public Library of Science, 2015)
BACKGROUND: Irritable bowel syndrome (IBS), a chronic functional condition, considerably reduces quality of life (QoL) and referral to gastroenterology is common. Until now, however, the impact of seeing a gastroenterologist for IBS on patients’ QoL and utility has not been assessed.